Non-suicidal self-injury and suicidal ideation among Chinese college students of childhood emotional abuse: associations with rumination, experiential avoidance, and depression - Wang, Wan; Wang, Xi; Duan, Guiqin (Frontiers in Psychiatry, 2023)
Background: Prior studies have proved the relationships between childhood emotional abuse (CEA) histories and suicidal thoughts or behaviors in adulthood, however, how emotion regulation strategies work as the mediating mechanism is necessary to be investigated. This study aimed to further verify the impacts of rumination, experiential avoidance (EA) and depression on the associations between CEA and non-suicidal self-injury (NSSI) and suicidal ideation (SI) on a sample of Chinese college students. Methods: The Childhood Emotional Abuse Questionnaire, the Non-Suicidal Self-Injury Questionnaire, the Symptom Checklist, the Ruminative Response Scale, the Acceptance and Action Questionnaire-II and the Zung Self-Rating Depression Scale were completed by 1,317 college students. Results: The rates of NSSI and SI of students with CEA experiences were 31.70% and 7.90% respectively, both higher than those without such experiences. The mediating roles of rumination, EA and depression between CEA and NSSI and SI were significant (p<0.01). Conclusions: The current study shed light on the linking roles of rumination, EA and depression in the relations between CEA and NSSI and SI. It is suggested that developing adaptive emotion-regulating strategies may be helpful to the intervention of suicidal thoughts or behaviors among individuals with CEA experiences.